2018
DOI: 10.1186/s12916-018-1072-0
|View full text |Cite
|
Sign up to set email alerts
|

Abortion-related emergency department visits in the United States: An analysis of a national emergency department sample

Abstract: BackgroundMedia depictions and laws passed in state legislatures regulating abortion suggest abortion-related medical emergencies are common. An accurate understanding of abortion-related emergencies is important for informing policy and practice. We assessed the incidence of abortion-related emergency department (ED) visits in the United States (U.S.).MethodsWe used a retrospective observational study design using 2009–2013 data from the Nationwide Emergency Department Sample, a nationally representative samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…None of the qualitative interview participants here reported that their selfmanaged abortion resulted in medical complications; however, we found in the survey of abortion patients that some women did report getting hit in the abdomen to try to end the pregnancy. Little is known about whether women are presenting to emergency departments or other clinical settings with medical complications after abortion self-induction; one study estimated 1.4% of abortion-related emergency department visits between 2009 and 2013 may be due to attempts at selfmanaged abortion [13].…”
Section: Discussionmentioning
confidence: 99%
“…None of the qualitative interview participants here reported that their selfmanaged abortion resulted in medical complications; however, we found in the survey of abortion patients that some women did report getting hit in the abdomen to try to end the pregnancy. Little is known about whether women are presenting to emergency departments or other clinical settings with medical complications after abortion self-induction; one study estimated 1.4% of abortion-related emergency department visits between 2009 and 2013 may be due to attempts at selfmanaged abortion [13].…”
Section: Discussionmentioning
confidence: 99%
“…We note that the numbers for these outcomes are very small and that cross-state comparisons should be interpreted with caution. In the case of self-induction, in particular, we believe that it is still important to describe women's experiences with self-induction because very little data exist (with few exceptions) (Grossman et al, 2010;Jerman, Onda, & Jones, 2018;Upadhyay et al, 2018) about women's experiences with self-induction, especially unsuccessful self-induction attempts after which women continue their pregnancies. We note that there are some inconsistencies in reporting around self-induction attempts, i.e., that a few women who said they attempted self-induction did not report considering abortion, pointing to the importance of future research on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…This is in part because complications are rare after abortion: one study in California of over 500,000 abortion patients in 2009–2010 found that 0.9% visited an ED for an abortion-related complication within 6 weeks of the abortion [ 14 ]. A national study found that 0.01% of all ED visits by women aged 15–49 in 2009–2013 were abortion-related, of which 51% required only observation without treatment [ 15 ]. Patients who travel farther to access abortion services are more likely to seek care in an ED in case of a possible complication after returning home, suggesting that as facility-based abortion care becomes more difficult to access—or even non-existent in some states—more patients may present to EDs for abortion-related care [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…National data suggest that ED visits related to SMA in particular are even less common, representing 1.4% of abortion-related ED visits. Higher rates of SMA-related ED visits were documented in the South (2%) compared to the Midwest (1%), West (1.1%), and Northeast (1.3%) [ 15 ]. There are research gaps in our understanding of the provision of SMA-related treatment in the hospital setting.…”
Section: Introductionmentioning
confidence: 99%